Ethephon as a potential tool to manage alternate bearing of ‘Fuji’ apple trees - da Silveira Pasa, Mateus; Carra, Bruno; Fontanella Brighenti, Alberto; Moretti Ferreira Pinto, Felipe Augusto; de Mello-Farias, Paulo Celso; Herter, Flávio Gilberto (Revista Ceres, 2025)
The objective of this study was to investigate the effect of different rates of ethephon on return bloom and yield, and fruit quality of ‘Fuji’ apple trees. The experiment was performed during the 2014/2015 and 2015/2016 growing seasons. Eighteen-year-old Fuji Standard apple trees grafted on M.9 were sprayed with different rates of ethephon (300 mg L-1, 400 mg L-1, and 500 mg L-1) 30 days after full bloom (DAFB) and compared to an unsprayed control. Yield components (number of fruit per tree, yield, fruit weight, and estimated yield) and fruit quality attributes (fruit firmness, total soluble solids and starch-iodine index) were evaluated in both seasons. Return bloom (percentage of flowering spurs and 1-year-shoots) was assessed only the year following the application. Our results show that ethephon increases return bloom and yield of ‘Fuji Standard’ apple trees, without affecting fruit quality attributes.